2016
DOI: 10.1016/j.apenergy.2016.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Environmental knowledge, pro-environmental behaviour and energy savings in households: An empirical study

Abstract: Energy consumption in households comprises over a quarter of total energy use in the UK [1]. Human behaviour is one of the main factors that can influence domestic energy consumption, together with the physical properties of the dwelling, climate, number and demographic profile of occupants, household income, lifestyle, and appliance ownership and use [2][3][4][5]. Indeed, variation in residents' behaviour can cause significant differences in energy consumption between dwellings with otherwise similar characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 279 publications
(151 citation statements)
references
References 62 publications
4
140
0
7
Order By: Relevance
“…China demonstrates a stable trend of reducing emissions intensity per economic output, despite an overall growth in living standards and non-industry consumer consumption, due to factors such as increased energy efficiency [93,94]. However, its high emission intensity per energy input in many of the industrial sectors is a determinant of technological structure being orientated towards high energy consumption [95].…”
Section: Discussionmentioning
confidence: 99%
“…China demonstrates a stable trend of reducing emissions intensity per economic output, despite an overall growth in living standards and non-industry consumer consumption, due to factors such as increased energy efficiency [93,94]. However, its high emission intensity per energy input in many of the industrial sectors is a determinant of technological structure being orientated towards high energy consumption [95].…”
Section: Discussionmentioning
confidence: 99%
“…Instead the key to changing energy consumption behaviour is through improved education so that consumers gain a full understanding of why energy conservation is imperative [26]. Pothitou, Hanna, and Hanna, conducted a study on the link between energy conservation and environmental knowledge, specifically considering domestic energy consumption [27]. This study found a positive correlation between environmental values, environmental knowledge and energy conservation [27].…”
Section: Qatar: Backgroundmentioning
confidence: 99%
“…Technological improvements, falling prices of new ICT entertainment appliances and greater demand for these products have led, through economies of scale, to increased production volumes and competition, leading to further price reductions and mass market saturation. This has resulted in the ownership of multiple entertainment appliances per home, for example, it is common for a household to own more than one TV and computer [58], as well as more than one phone, DVD-player and games console [56].…”
Section: The Market Growth Of Home Entertainment Appliancesmentioning
confidence: 99%